Differentiated LKPD Writing Assistance for English Teachers in South OKU Regency, South Sumatra: Pendampingan Penulisan LKPD Berdiferensiasi bagi Guru Bahasa Inggris di Kabupaten OKU Selatan, Sumatera Selatan - Anggraini, Hesti Wahyuni; Sofendi, Sofendi; Vianty, Machdalena; Amrullah, Amrullah; Silvhiany, Sary; Yazir, Muhammad (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
In differentiated learning, teachers need to develop student worksheets tailored to the profile of the students. One of the challenges in the English language learning process in the target area is the limited availability of worksheets that align with the students' readiness levels. This mentoring activity aims to enhance the skills of 25 English teachers in OKU Selatan District, South Sumatra, in developing differentiated worksheets tailored to students' readiness levels. Conducted online and offline over 40 hours, the activity includes presentations and worksheet design development, with feedback from experts. Results show teachers are enthusiastic and able to produce differentiated worksheet designs. The activity seeks to address the limited availability of worksheets aligned with students' readiness levels, ultimately improving English language learning quality in the target area. Future continuations of this activity are expected to further enhance teaching skills and student outcomes.